A New Species of the Genus Paramicroplus (Coleoptera, Scarabaeidae, Melolonthinae, Hopliini) from Madagascar - Vasko, B. M. (Zoodiversity, 2025)
An illustrated description and diagnosis of Paramicroplus keithi sp. n. and an updated key to the species of the genus Paramicroplus Lacroix, 1998 are provided. The new species is similar to P. vitellinus Lacroix, 1998, differing by the slightly larger body size, the shape of clypeus, the peculiar shape of aedeagus, and other characteristics.